2024
DOI: 10.1021/acsenvironau.3c00055
|View full text |Cite
|
Sign up to set email alerts
|

Per/Polyfluoroalkyl Substances (PFASs) in a Marine Apex Predator (White Shark, Carcharodon carcharias) in the Northwest Atlantic Ocean

Jennifer Marciano,
Lisa Crawford,
Leenia Mukhopadhyay
et al.

Abstract: Per/polyfluoroalkyl substances (PFASs) are ubiquitous, highly persistent anthropogenic chemicals that bioaccumulate and biomagnify in aquatic food webs and are associated with adverse health effects, including liver and kidney diseases, cancers, and immunosuppression. We investigated the accumulation of PFASs in a marine apex predator, the white shark (Carcharodon carcharias). Muscle (N = 12) and blood plasma (N = 27) samples were collected from 27 sharks during 2018−2021 OCEARCH expeditions along the eastern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Sharks are meso-to-apex predators, have diverse functional roles, and are often considered sentinels for evaluating the overall health of marine ecosystems. Due to their potential longevity, slow growth, large size, and high trophic level, the tissues of many shark species have been found to contain relatively high concentrations of diverse persistent organic pollutants (e.g., polychlorinated biphenyls [PCBs], dichloro-diphenyl-trichloroethane [DDT], and methylmercury [MeHg]) owing to prolonged bioaccumulation and biomagnification. However, only a handful of studies have reported PFAS concentrations in sharks (e.g., blue sharks (Prionace glauca), tiger sharks (Galeocerdo cuvier), bull sharks (Carcharhinus leucas), and white sharks (Carcharodon carcharias)) sampled from the Mediterranean Sea, Atlantic, and Indian Oceans, which often contain long-chain PFAS. For example, perfluorotridecanoic acid (PFTrDA), perfluoroundecanoic acid (PFUnA), and perfluorooctanesulfonate (PFOS) were predominant compounds in muscle tissue, followed by perfluorotetradecanoic acid (PFTA) and perfluorododecanoic acid (PFDoA). ,, On average, total detected concentrations of PFAS (∑PFAS) ranged from 0.14 to 17.9 ng g –1 (wet weight, ww; muscle tissue), with the highest concentration detected in angular roughsharks (Oxynotus centrina) sampled in the Mediterranean Sea .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sharks are meso-to-apex predators, have diverse functional roles, and are often considered sentinels for evaluating the overall health of marine ecosystems. Due to their potential longevity, slow growth, large size, and high trophic level, the tissues of many shark species have been found to contain relatively high concentrations of diverse persistent organic pollutants (e.g., polychlorinated biphenyls [PCBs], dichloro-diphenyl-trichloroethane [DDT], and methylmercury [MeHg]) owing to prolonged bioaccumulation and biomagnification. However, only a handful of studies have reported PFAS concentrations in sharks (e.g., blue sharks (Prionace glauca), tiger sharks (Galeocerdo cuvier), bull sharks (Carcharhinus leucas), and white sharks (Carcharodon carcharias)) sampled from the Mediterranean Sea, Atlantic, and Indian Oceans, which often contain long-chain PFAS. For example, perfluorotridecanoic acid (PFTrDA), perfluoroundecanoic acid (PFUnA), and perfluorooctanesulfonate (PFOS) were predominant compounds in muscle tissue, followed by perfluorotetradecanoic acid (PFTA) and perfluorododecanoic acid (PFDoA). ,, On average, total detected concentrations of PFAS (∑PFAS) ranged from 0.14 to 17.9 ng g –1 (wet weight, ww; muscle tissue), with the highest concentration detected in angular roughsharks (Oxynotus centrina) sampled in the Mediterranean Sea .…”
Section: Introductionmentioning
confidence: 99%
“… 31 Concentrations of ∑PFAS in basking sharks ( Cetorhinus maximus ) also varied among tissue types and were higher in skin and liver than in muscle. 28 One recent study reported higher ∑PFAS concentrations in blood plasma than in muscle tissue of white sharks in the Northwest Atlantic Ocean, 30 and another recent study revealed interspecific variation in the ∑PFAS of plasma in four small coastal shark species along the South Atlantic Bight. 32 While intertissue differences in PFAS are common in sharks, additional drivers of bioaccumulation patterns remain speculative.…”
Section: Introductionmentioning
confidence: 99%